2015
DOI: 10.1111/sji.12343
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 Deficiency Leads to Altered BCR Signalling Revealed by Enhanced PI3K Pathway, Decreased SHIP Expression and Defected Cytoskeletal Responses

Abstract: The graded expression of transcription factor interferon regulatory factor 4 (IRF4) regulates B cell development and is critical for plasma cell differentiation. However, the mechanisms, by which IRF4 elicits its crucial tasks, are largely unknown. To characterize the molecular targets of IRF4 in B cells, we established an IRF4-deficient DT40 B cell line. We found that in the absence of IRF4, the expression of several molecules involved in BCR signalling was altered. For example, the expression of B cell adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…The resulting DKO cells were verified to lack both the IRF4 and BCL6 expression (Figure A,B). BCL6 and IRF4 single knockouts were described previously . The DKO cell line had the same growth characteristics as IRF4 single knockout and WT cell lines (Figure ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The resulting DKO cells were verified to lack both the IRF4 and BCL6 expression (Figure A,B). BCL6 and IRF4 single knockouts were described previously . The DKO cell line had the same growth characteristics as IRF4 single knockout and WT cell lines (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…BCL6 and IRF4 single knockouts were described previously. 4,17 The DKO cell line had the same growth characteristics as IRF4 single knockout and WT cell lines ( Figure S1). As BCL6KO cells secrete antibodies, 4 we analysed whether DKO cells lacking both IRF4 and BCL6 also secrete.…”
Section: Infection Of Cells By Lentiviral Constructsmentioning
confidence: 94%
See 2 more Smart Citations
“…In detail, we found that all three tumor infiltrating B lymphocytes (TIL-B) subsets, activated or effector memory CD8+ and activated or effector memory CD4+T cells were significantly correlated with IRF4 expression (|r| > 0.3 and P < 0.001) (Figure 4). In fact, several studies showed that IRF4 plays a key role in diverse pathways related immune cell (21)(22)(23)(24)(25). Above all, high IRF4 expression might be reflect a state having predominantly tumor-specific TILs which play an important role in tumor control and prevent tumor progression (26).…”
Section: Discussionmentioning
confidence: 99%